Nonlocal problems for controllability of functional differential equation. Issue 2 (July 2021) - Selvamani, C; Loganathan, C
Abstract: The present work addresses the nonlocal problems for a controllability of functional differential equation in Banach spaces. Sufficient conditions are derived by using Schaefer's fixed point and semigroup theory.